Etiology of bacterial and parasitological pediatric diarrhoea in a tertiary care hospital - Panda, Animesh; Chandrakar, Shiv Kumar; Bawankar, Smita; Chandi, Dhruba Hari (Asian Journal of Medical Sciences, 2016)
Background : Before starting to discuss about Diarrhoea, we have to remember diarrhoea is one of the main causes of morbidity and mortality in children. Aims and Objectives : The aim of this study was to determine the prevalence of intestinal parasitic and bacterial infections as cause of childhood diarrhoea. Materials and Methods : During the study period, a total of 116 stool samples were collected and processed. Examined grossly and microscopically for presence of ova/cyst. They were also cultured on MacConkey agar and E. coli isolated were identified by standard biochemical tests. Results : Out of 116 stools samples, Entamoeba histolytica (63.33%) and Giardia lamblia (23.33%) were more common parasitic cause diarrhoea among children by either ova or cyst. E.coli (74.13%) was common bacterial cause of diarrhoea among children. E. coli isolated in pure culture and sent for sero typing to Central Research Institute (CRI), Kasauli. Maximum percent were found to be pathogenic Escherichia coli i.e. EPEC 22.5%. Conclusion : According to the result, the most common cause of bacterial diarrhoea is E.coli. EPEC were more prevalent followed by EHEC. Thus, macroscopic and microscopic stool examinations as well as culture were important for finding out the course of diarrhoea in childhood. Asian Journal of Medical Sciences Vol. 7(3) 2016 54-57